Association of age at menopause and suicide risk in postmenopausal women: a nationwide cohort study - Moon, Daa Un; Kim, Hyewon; Jung, Jin-Hyung; Han, Kyungdo; Jeon, Hong Jin (Frontiers in Psychiatry, 2024)
IntroductionEarly age at menopause has been linked to various adverse health outcomes, but its association with suicide risk remains underexplored. This study aims to assess the relationship between age at menopause and suicide risk among postmenopausal women.MethodsThis retrospective cohort study analyzed data from the Korean National Health Insurance System (NHIS), covering 1,315,795 postmenopausal women aged 30 years and above, from 2009 to 2021. Menopausal age was classified as primary ovarian insufficiency (under 40 years), early menopause (40-44 years), average menopause (45-49 and 50-54 years), and late menopause (55 years and older). Suicide incidence was identified using ICD-10 codes for primary cause of death. Multivariable Cox proportional hazards models were utilized to estimate hazard ratios (HRs) and 95% confidence intervals (CIs).ResultsAcross the 12-year follow-up, there were 2,986 suicides. Women with primary ovarian insufficiency exhibited the highest suicide risk (HR, 1.43; 95% CI, 1.14–1.78, p < 0.001), followed by those with early menopause (HR, 1.31; 95% CI, 1.15–1.50, p < 0.001), and those with menopause between 45 and 49 (HR, 1.13; 95% CI, 1.04–1.23, p < 0.001) compared to the reference group undergoing menopause at age of 50-54.DiscussionEarly onset of menopause, particularly primary ovarian insufficiency, is associated with a significantly elevated risk of suicide. These findings underscore the need for targeted interventions and support for women experiencing early menopause. This study highlights the importance of monitoring mental health in postmenopausal women and suggests further research to explore the underlying mechanisms linking early menopause to increased suicide risk.